(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents the results of the phenological phases of cherry plum vegetation in the conditions of the Chui valley of Kyrgyzstan. Observations were carried out on 28 varieties of cherry plum from the collection of the Botanical Garden. The results of the introduction of wildgrowing cherry plum and cultivars are presented.